Role of Growth Regulators on Quality and Yield of Kalmegh (Andrographis paniculata Nees) - Shekhada, Raxit R.; Macwan, Sunil J.; Patel, Nilesh J.; Gajbhiye, Narendra A. (International Journal of Economic Plants, 2022)
Astudy was conducted at B.A.College of Agriculture,Anand Agricultural University,Anand during 2019 to find out the influence of foliar treatments on the productivity of Kalmegh.Different treatments which includes T1 (NAA 50 mg l-1), T2 (NAA 100 mg l-1),T3 (NAA 200 mg l-1), T4 (GA3 50 mg l-1), T5 (GA3 100 mg l-1), T6 (GA3 200 mg l-1), T7 (paclobutrazol 50 mg l-1), T8 (paclobutrazol 100 mg l-1), T9 (paclobutrazol 200 mg l-1) and T10 (control) were applied as foliar at 30 days after transplanting. The effect of phytohormones on dry herbage yield at harvest were found significant and highest was (4913.84 kg ha-1) in GA3 100 mg l-1 followed by paclobutrazol 100 mg l-1(4901.68 kg ha-1) and paclobutrazol 200 mg l-1 (4884.48 kg ha-1) as compared to control. Andrographolide content (%) at harvest were recorded significant and highest was (1.453%) observed in GA3 200 mg l-1. Higher andrographolide content was recorded in GA3 100 mg l-1 (1.403%) and paclobutrazol 100 mg l-1 (1.395%). Results indicated that increased the content of andrographolide by 25.04%, 20.74% and 20.05% in case of GA3 200 mg l-1, GA3 100 mg l-1 and paclobutrazol 100 mg l-1 respectivelyas compared to control. Growth parameters leaf dry weight (0.688) and total dry weight (0.654) reported positive significant correlation with quality parameter i.e.andrographolide percentage at harvest.Physiological parameter have positive significant correlation with the quality i.e. andrographolide viz.SLW (0.699), RGR (0.677), CGR (0.692), NAR (0.655) and BMD (0.651).